Sedimentary basins of continental margins and cratons - Bott, Martin Harold Phillips, 1926- (Developments in geotectonics, 1976)
Developments in Geotectonics, 12: Sedimentary Basins of Continental Margins and Cratons focuses on the formation, movements, characteristics, and evolution of sedimentary basins of continental margins and cratons. The selection first offers information on mechanisms of basin subsidence and rheology of the lithosphere. Discussions focus on hypotheses of basin subsidence mechanism, testing the hypotheses, elastic properties and flexural rigidity of the lithosphere, and rheology of young continental margins. The text then elaborates on flexure of the lithosphere and continental margin basins and.